An Econometric Model of Pronatalist and Abortion Policies - Coelen, Stephen P.; McIntyre, Robert J. (Journal of Political Economy, 1978)
The relationship between population policy instruments and fertility levels in Hungary is analyzed with a simultaneous equation model. Both birth and abortion relationships are placed in a supply and demand perspective, permitting a distinction between desired and actual levels of births and abortions. Pronatalist and abortion policies are evaluated through the reduced forms of the structural equations. Effects of average earnings, income, value of time spent at home, and speed of adjustment to policy changes are also considered. The analytical method is thought to permit appraisal of the effects of population policy in both developed and developing countries